2014
DOI: 10.1016/j.jsat.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A performance measure for continuity of care after detoxification: Relationship with outcomes

Abstract: Administrative data from five states were used to examine whether continuity of specialty substance abuse treatment after detoxification predicts outcomes. We examined the influence of a 14-day continuity of care process measure on readmissions. Across multiple states, there was support that clients who received treatment for substance use disorders within 14-days after discharge from detoxification were less likely to be readmitted to detoxification. This was particularly true for reducing readmissions to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The use of illicit and misuse of licit substances remains a substantial population health concern in rural America. [1][2][3] Continuity into follow-up treatment for a substance use disorder (SUD) within the 1 or 2 weeks after discharge from detoxification [4][5][6][7] or residential treatment 8,9 is associated with improved outcomes, yet the majority of clients do not even begin this continuing treatment. [10][11][12] Access to continuing care is especially limited in rural and non metropolitan areas, [13][14][15][16][17][18] an issue of particular importance since failure to receive adequate treatment can contribute to the burden of SUDs in rural America.…”
Section: Discussionmentioning
confidence: 99%
“…The use of illicit and misuse of licit substances remains a substantial population health concern in rural America. [1][2][3] Continuity into follow-up treatment for a substance use disorder (SUD) within the 1 or 2 weeks after discharge from detoxification [4][5][6][7] or residential treatment 8,9 is associated with improved outcomes, yet the majority of clients do not even begin this continuing treatment. [10][11][12] Access to continuing care is especially limited in rural and non metropolitan areas, [13][14][15][16][17][18] an issue of particular importance since failure to receive adequate treatment can contribute to the burden of SUDs in rural America.…”
Section: Discussionmentioning
confidence: 99%
“…21 Current Procedural Terminology (CPT) and Healthcare Common Procedure Coding System (HCPCS) codes, place of service, and primary substance use or mental disorder diagnosis were used to identify residential behavioral health treatment (RES), excluding detoxification; partial hospital or intensive outpatient program (IOP); outpatient behavioral health services (OP); and MAT, defined as a prescription fill of buprenorphine, disulfiram, acamprosate, or naltrexone or a HCPCS service code for methadone, buprenorphine, or naltrexone.…”
Section: Methodsmentioning
confidence: 99%
“…12 Receiving addiction treatment soon after discharge is associated with reduced detoxification readmission, 20,21 with stronger findings for residential than outpatient. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Over a fifth of annual admissions to SUD treatment are for detox (Center for Behavioral Health Statistics and Quality, 2014). Studies have shown that continuity of care after detox is associated with better outcomes, including reduced detox readmission (Lee et al, 2014; Mark, Vandivort-Warren, & Montejano, 2006). However, many receiving detox services do not receive follow-up treatment.…”
Section: Introductionmentioning
confidence: 99%